PENDEKATAN SAINTIFIK TERHADAP KOMPETENSI KONSEP ENERGI PANAS PADA ANAK TUNARUNGU - Diah Ekawati, Novia (Jurnal Pendidikan Khusus, 2016)
ABSTRACT Hearing impairment had impact to hearing impairment children’s academic ability so that it caused the knowledge competence (K3) which emphasized to the comprehension of hearing impairment children about heat energy concept very less. Therefore, to solve the problem it required an effective approach which was adjusted to the characteristics and the needs of hearing impairment children, one of them was by applying scientific approach in learning process. The purpose of this research was to know whether there was the influence of scientific approach toward heat energy concept competence to hearing impairment children or not. The research method used was quantitative method with pre-experiment arrangement and the kind of one group pre test post test design. The research result indicated that in the result of pre test the average value was 27 and post test was 77. The result of data analysis indicated that the value of T counted (17,597) ≥ T table (2,045) with significant level 5%. It could be concluded that Ha was accepted it meant that there was influence of scientific approach application toward heat energy concept competence to hearing impairment children.   Keywords: Scientific approach, heat energy concept